2020
DOI: 10.1515/biol-2020-0008
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Promoting Rhizobacteria (PGPR) Regulated Phyto and Microbial Beneficial Protein Interactions

Abstract: AbstractPlant Growth Promoting Rhizobacteria (PGPR) influence plants’ physiological characteristics, metabolites, pathways and proteins via alteration of corresponding gene expression. In the current study, a total of 42 upregulated uncharacterized sorghum bicolor root proteins influenced by PGPR were subjected to different analyses: phylogenetic tree, protein functional network, sequences similarity network (SSN), Genome Neighborhood Network (GNN) and motif analysis. The scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Phytobeneficial characteristics were modulated by reciprocal protein activation via microbe-plant interactions during and after colonization by PGPR. Furthermore, bacterial gene regulators linked to bacterial signaling, DNA binding transcriptional regulators, and cell proliferation were induced by plant root exudates [93]. Climate change has a significant impact on the efficiency of PGPR, yet unfavorable growing circumstances in the field are to be expected as part of the routine operation of agriculture [94].…”
Section: Pgpr's Effects On Regulated Phyto and Microbial Beneficial Protein Interactionsmentioning
confidence: 99%
“…Phytobeneficial characteristics were modulated by reciprocal protein activation via microbe-plant interactions during and after colonization by PGPR. Furthermore, bacterial gene regulators linked to bacterial signaling, DNA binding transcriptional regulators, and cell proliferation were induced by plant root exudates [93]. Climate change has a significant impact on the efficiency of PGPR, yet unfavorable growing circumstances in the field are to be expected as part of the routine operation of agriculture [94].…”
Section: Pgpr's Effects On Regulated Phyto and Microbial Beneficial Protein Interactionsmentioning
confidence: 99%
“…Pseudomonas sp. is also reported to regulate protein synthesis, seed germination, siderophore production and phyto-beneficial traits (Zhang et al, 2019, Dhawi, 2020. Previous studies have also revealed that combined inoculation of A. Brailense with Pseudomonas sp.…”
Section: Resultsmentioning
confidence: 98%
“…Some important traits sustain plants under biotic and abiotic types of stress (140). Advanced bioinformatic studies indicate reciprocal gene regulation between bacteria and their host plants during colonization and post colonization also (141). Phyto-beneficial proteins have been reported to induce in sorghum roots after PGPR inoculation (141).…”
Section: Molecular Responses and Signalling Pathways In Response To P...mentioning
confidence: 99%
“…Advanced bioinformatic studies indicate reciprocal gene regulation between bacteria and their host plants during colonization and post colonization also (141). Phyto-beneficial proteins have been reported to induce in sorghum roots after PGPR inoculation (141). Some phyto-beneficial proteins deal with DNA regulation including Phosphodiesterase, sulfatase, Carbohydrate kinases (FGGY_C) whereas some of these are stress relieving in nature such as HSP70 (141).…”
Section: Molecular Responses and Signalling Pathways In Response To P...mentioning
confidence: 99%
See 1 more Smart Citation